High-energy-storage modified BNNS / PTFE composite film and preparation method thereof
By combining polydopamine on BNNS and grafting silane coupling agent, BNNS is modified to improve its dispersion and interface binding in PTFE matrix, the problem of poor interface binding between BNNS and PTFE matrix is solved, and the composite film is realized High dielectric performance and high temperature energy storage performance.
Patent Information
- Application Number
- CN202411275648.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-02-07
AI Technical Summary
When BNNS is directly added to the PTFE-based energy storage film, the interface bond between BNNS and the PTFE matrix is poor, limiting the improvement of the energy storage performance of composite materials.
By combining polydopamine on boron nitride nanosheets and grafting silane coupling agent, the boron nitride nanosheets are modified to improve their dispersion and interface combination in the PTFE matrix, thereby improving energy storage performance.
The modified BNNS/PTFE composite film exhibits high dielectric properties and high-temperature energy storage performance, effectively solving the problem of poor interface bonding between BNNS and PTFE matrix.
Smart Images

Figure CN119391111A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of dielectric energy storage materials, and in particular to a high-energy storage modified BNNS / PTFE composite film and a preparation method thereof. Background Art
[0002] Compared with traditional electrochemical energy storage systems (lithium-ion batteries, fuel cells, supercapacitors), dielectric materials can charge and discharge faster and have higher efficiency. They have also received more extensive attention due to their potential functions in advanced equipment such as lasers, microwaves, railguns, and electromagnetic catapult technology with high energy storage and power density.
[0003] Energy storage films often use composite materials of polymers and inorganic fillers. Hexagonal boron nitride (h-BN) is a wide bandgap insulating material with a high dielectric constant and breakdown strength. After it is made into boron nitride nanosheets (BNNS), it can further improve the breakdown strength and mechanical modulus. When added to polymer films, it can improve the energy storage performance of polymer films by establishing conduction barriers and breakdown barriers.
[0004] For example, patent CN108300153A discloses high energy storage density dielectric materials and preparation methods thereof, which achieve good energy storage performance by adding inorganic fillers such as boron nitride nanosheets to an organic matrix (such as polytetrafluoroethylene, etc.). However, these prior arts have the following problems: when BNNS is directly added to a polytetrafluoroethylene (PTFE)-based energy storage film, the interface bonding between BNNS and the PTFE matrix is poor, which limits the improvement of the energy storage performance of the composite material. Summary of the invention
[0005] In order to solve the above technical problem, that is, when BNNS is directly added to a PTFE-based energy storage film, the effect of improving the energy storage performance of the film is limited, the present invention provides a high energy storage modified BNNS / PTFE composite film and a preparation method thereof. The composite film can improve the effect of BNNS therein and achieve better dielectric properties and high-temperature energy storage performance.
[0006] The specific technical scheme of the present invention is: In the first aspect, the present invention provides a high energy storage modified BNNS / PTFE composite film, comprising a polytetrafluoroethylene matrix and modified boron nitride nanosheets dispersed in the polytetrafluoroethylene matrix; the modified boron nitride nanosheets comprise boron nitride nanosheets, polydopamine bound to the boron nitride nanosheets, and a silane coupling agent grafted onto the polydopamine; the silane coupling agent comprises a fluorine-containing silane coupling agent and an aminosilane coupling agent containing at least one amino group and at least one imine group.
[0007] Since the boron nitride nanosheets only have a small amount of hydroxyl groups at the edges or defects, the present invention first combines polydopamine on the surface thereof to introduce more hydroxyl groups, and then grafts silane coupling agents, so that more silane coupling agents can be connected to the modified boron nitride nanosheets. By using these silane coupling agents, the dispersibility of BNNS in PTFE emulsion can be improved during film making, and the interface bonding between BNNS and PTFE matrix can be enhanced, thereby improving the effect of BNNS on improving the energy storage performance of PTFE film, so that the modified BNNS / PTFE composite film has higher dielectric properties and high-temperature energy storage performance.
[0008] In addition, the present invention adopts a compound of two specific silane coupling agents (a fluorinated silane coupling agent and an aminosilane coupling agent containing at least one amino group and at least one imine group), which can produce a synergistic effect of "1+1>2" and further improve the high-temperature energy storage performance of the composite film. Specifically: the use of a fluorinated silane coupling agent can enhance the interaction force between molecules inside the composite film and affect the crystallization behavior of the material, thereby reducing the mobility of the molecular chains in the composite film at high temperatures, so that the film has a smaller free volume at high temperatures and has a shorter free charge acceleration path under an external electric field. Therefore, the kinetic energy of free charges at high temperatures is low, which is conducive to reducing losses and improving the high-temperature energy storage performance of the composite film; the aminosilane coupling agent containing amino and imine groups has stronger alkaline properties and can stably bond with the fluorine atoms on the polymer molecular chain. This bonding action not only enhances the interaction between the aminosilane coupling agent and the polymer molecular chain, but also can fix the polymer molecular chain in an appropriate position. Since the strength of this bonding action is much greater than the ordinary physical interaction force, it can limit the mobility of the polymer molecular chain at high temperatures, thereby improving its high-temperature energy storage performance. Through the above mechanism, the fluorine-containing silane coupling agent and aminosilane coupling agent present on the modified boron nitride nanosheets can act on different positions in the PTFE molecular chain in different ways, thereby limiting the movement of the PTFE molecular chain to a greater extent and improving the high-temperature energy storage performance of the composite film.
[0009] Preferably, the fluorinated silane coupling agent contains a perfluoroalkyl group having 6 to 8 carbon atoms.
[0010] In fluorinated silane coupling agents, when the carbon chain length of the perfluoroalkyl group is too short, the effect of reducing the ability of the molecular chain in the composite film to move at high temperature is poor, which is not conducive to the improvement of the high-temperature energy storage performance of the film; when the carbon chain length of the perfluoroalkyl group is too long, the carbon chain is prone to decomposition or breakage at high temperature, affecting its ability to restrict the movement of the polymer molecular chain, and also reducing the high-temperature energy storage performance of the film. The present invention controls the carbon chain length of the perfluoroalkyl group to C6-8, which can improve the high-temperature energy storage performance of the composite film to a greater extent.
[0011] Preferably, the molar ratio of the fluorine-containing silane coupling agent to the aminosilane coupling agent is 1:4.5-5.5.
[0012] When the ratio between the fluorinated silane coupling agent and the amino silane coupling agent is too large or too small, the synergistic effect between the two will be affected, thereby affecting the high-temperature energy storage performance of the composite film. The present invention controls the molar ratio of the two within the range of 1:4.5 to 5.5, which can give the composite film better high-temperature energy storage performance.
[0013] Preferably, the aminosilane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (KH792).
[0014] Preferably, the mass ratio of the polytetrafluoroethylene matrix to the modified boron nitride nanosheets is 100:0.03-0.06.
[0015] In a second aspect, the present invention provides a method for preparing the high energy storage modified BNNS / PTFE composite film, comprising the following steps: (1) Boron nitride nanosheets and dopamine monomers are used as raw materials to carry out a polymerization reaction, and polydopamine (PDA) is compounded on the surface of the boron nitride nanosheets to obtain a BNNS / PDA composite; (2) Grafting the silane coupling agent onto the BNNS / PDA composite through a dehydration condensation reaction between hydroxyl groups and siloxy groups to obtain modified boron nitride nanosheets; (3) The modified boron nitride nanosheets are composited with polytetrafluoroethylene to form a film.
[0016] Preferably, the preparation method specifically comprises the following steps: (1) dispersing boron nitride nanosheets and dopamine monomers in a reaction solvent, reacting at 25-30° C. for 10-15 hours to obtain a BNNS / PDA composite dispersion; (2) adding a silane coupling agent to the BNNS / PDA composite dispersion, reacting at 80-90° C. for 5-8 hours, separating the product, and dispersing it in a dispersion medium to obtain a modified boron nitride nanosheet dispersion; (3) The polytetrafluoroethylene emulsion and the modified boron nitride nanosheet dispersion are mixed, coated on a substrate, and after heat treatment and cooling, the obtained film is peeled off from the substrate.
[0017] Preferably, in step (1), the mass ratio of the boron nitride nanosheets to the dopamine monomer is 1:0.08-0.15; the mass ratio of the boron nitride nanosheets in step (1) to the silane coupling agent in step (2) is 1:0.1-0.3.
[0018] Preferably, in step (1), the dopamine monomer is dopamine hydrochloride.
[0019] Preferably, in step (1), the mass volume ratio of the boron nitride nanosheets to the reaction solvent is 1 g: 5 to 15 mL.
[0020] Preferably, in step (3), before mixing the polytetrafluoroethylene emulsion and the modified boron nitride nanosheet dispersion, a thickener is first added to the polytetrafluoroethylene emulsion.
[0021] Furthermore, the thickener is polyoxyethylene lauryl ether.
[0022] Preferably, in step (3), the volume ratio of the polytetrafluoroethylene emulsion to the modified boron nitride nanosheet dispersion is 1:0.03-0.05.
[0023] Preferably, in step (3), the heat treatment process includes: drying at 45-50°C for 1-2h, heating to 235-245°C at a rate of 90-110°C / h and keeping warm for 20-25min, then heating to 345-355°C at a rate of 55-65°C / h, and finally heating to 375-385°C at a rate of 90-110°C / h and keeping warm for 40-50min.
[0024] Compared with the prior art, the present invention has the following advantages: (1) In the present invention, by combining polydopamine on the boron nitride nanosheets and then grafting a silane coupling agent, the BNNS can be better dispersed in the PTFE matrix, and the interface bonding between the two is enhanced, thereby improving the effect of the BNNS and giving the composite film better dielectric properties and high-temperature energy storage performance.
[0025] (2) In the present invention, the use of a fluorine-containing silane coupling agent in combination with an aminosilane coupling agent containing at least one amino group and at least one imine group can produce a synergistic effect, thereby reducing the free volume in the film at high temperature to a greater extent, shortening the free charge acceleration path under an external electric field, and thereby improving the high-temperature energy storage performance of the composite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The dielectric spectra of the composite films with different addition amounts of modified BNNS are shown in Figure 1. Note: "3-792BNNS / PTFE", "4-792BNNS / PTFE" and "5-792BNNS / PTFE" are composite films prepared according to Example 2, Example 1 and Example 3, respectively.
[0027] Figure 2The energy storage density and energy storage efficiency of the composite film at 200°C and 250°C vary with field strength when different amounts of modified BNNS are added. Note: "3-792BNNS / PTFE", "4-792BNNS / PTFE", and "5-792BNNS / PTFE" are composite films prepared according to Example 2, Example 1, and Example 3, respectively. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the embodiments.
[0029] Overall embodiment A high energy storage modified BNNS / PTFE composite film comprises a polytetrafluoroethylene matrix and modified boron nitride nanosheets dispersed in the polytetrafluoroethylene matrix; the modified boron nitride nanosheets comprise boron nitride nanosheets, polydopamine bonded to the boron nitride nanosheets and a silane coupling agent grafted to the polydopamine; the silane coupling agent comprises a fluorine-containing silane coupling agent and an aminosilane coupling agent containing at least one amino group and at least one imine group.
[0030] As a specific implementation, the fluorine-containing silane coupling agent contains a perfluoroalkyl group with 6 to 8 carbon atoms.
[0031] As a specific implementation, the molar ratio of the fluorine-containing silane coupling agent to the aminosilane coupling agent is 1:4.5-5.5.
[0032] As a specific implementation, the aminosilane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0033] As a specific implementation manner, the mass ratio of the polytetrafluoroethylene matrix to the modified boron nitride nanosheets is 100:0.03-0.06.
[0034] A method for preparing the high energy storage modified BNNS / PTFE composite film comprises the following steps: (1) Boron nitride nanosheets and dopamine monomers are used as raw materials to carry out a polymerization reaction, and polydopamine is compounded on the surface of the boron nitride nanosheets to obtain a BNNS / PDA complex; (2) Grafting the silane coupling agent onto the BNNS / PDA composite through a dehydration condensation reaction between hydroxyl groups and siloxy groups to obtain modified boron nitride nanosheets; (3) The modified boron nitride nanosheets are composited with polytetrafluoroethylene to form a film.
[0035] As a specific implementation, the preparation method specifically comprises the following steps: (1) dispersing boron nitride nanosheets and dopamine monomers in a reaction solvent, reacting at 25-30° C. for 10-15 hours to obtain a BNNS / PDA composite dispersion; (2) adding a silane coupling agent to the BNNS / PDA composite dispersion, reacting at 80-90° C. for 5-8 hours, separating the product, and dispersing it in a dispersion medium to obtain a modified boron nitride nanosheet dispersion; (3) The polytetrafluoroethylene emulsion and the modified boron nitride nanosheet dispersion are mixed, coated on a substrate, and after heat treatment and cooling, the obtained film is peeled off from the substrate.
[0036] As a specific implementation, in step (1), the mass ratio of the boron nitride nanosheets to the dopamine monomer is 1:0.08-0.15.
[0037] As a specific implementation, the mass ratio of the boron nitride nanosheets in step (1) to the silane coupling agent in step (2) is 1:0.1-0.3.
[0038] As a specific implementation, in step (1), the dopamine monomer is dopamine hydrochloride.
[0039] As a specific implementation, in step (1), the mass volume ratio of the boron nitride nanosheets to the reaction solvent is 1g:5-15mL.
[0040] As a specific implementation, in step (3), before mixing the polytetrafluoroethylene emulsion and the modified boron nitride nanosheet dispersion, a thickener is first added to the polytetrafluoroethylene emulsion.
[0041] As a specific implementation, in step (3), the volume ratio of the polytetrafluoroethylene emulsion to the modified boron nitride nanosheet dispersion is 1:0.03-0.05.
[0042] As a specific implementation, in step (3), the heat treatment process includes: drying at 45-50°C for 1-2h, heating to 235-245°C at a rate of 90-110°C / h and keeping warm for 20-25min, then heating to 345-355°C at a rate of 55-65°C / h, and finally heating to 375-385°C at a rate of 90-110°C / h and keeping warm for 40-50min. Specific embodiments The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0044] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.
[0045] In the following embodiments, the abbreviations involved have the following meanings: KH792: N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; KH540: γ-aminopropyltrimethoxysilane; KH550: γ-aminopropyltriethoxysilane; h-BN: hexagonal boron nitride; BNNS: Boron Nitride Nanosheets; Tris: tris(hydroxymethyl)aminomethane; PTFE: polytetrafluoroethylene; PI: Polyimide.
[0046] Example 1 The modified BNNS / PTFE composite film was prepared by the following steps: (1) BNNS peeling: 4 g of h-BN powder was weighed and dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0047] (2) Modification of BNNS: 2.5 g BNNS and 0.255 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. Then, the mixture was stirred at 25 ° C for 12 h, and the temperature was raised to 80 ° C. 0.17 mmol heptafluorodecyltrimethoxysilane and 0.87 mmol KH792 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 ° C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0048] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0049] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0050] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0051] Example 2 The difference between this embodiment and embodiment 1 is that the amount of modified BNNS added is reduced in this embodiment. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this embodiment are as follows: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0052] (2) Modification of BNNS: 2.5 g BNNS and 0.255 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. Then, the mixture was stirred at 25 ° C for 12 h, and the temperature was raised to 80 ° C. 0.17 mmol heptafluorodecyltrimethoxysilane and 0.87 mmol KH792 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 ° C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0053] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 6 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0054] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0055] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0056] Example 3 The difference between this embodiment and embodiment 1 is that the amount of modified BNNS added in this embodiment is increased. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this embodiment are as follows: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0057] (2) Modification of BNNS: 2.5 g BNNS and 0.255 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. Then, the mixture was stirred at 25 ° C for 12 h, and the temperature was raised to 80 ° C. 0.17 mmol heptafluorodecyltrimethoxysilane and 0.87 mmol KH792 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 ° C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0058] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 10 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0059] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0060] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0061] Example 4 The modified BNNS / PTFE composite film was prepared by the following steps: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0062] (2) Modification of BNNS: Weigh 2.5 g BNNS and 0.2 g dopamine hydrochloride, add them to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicate for 30 min. Then stir at 25 ° C for 12 h, heat to 80 ° C, add 0.48 mmol heptafluorodecyltrimethoxysilane and 2.16 mmol KH792, and stir at 1200 rpm for 6 h. After the reaction, wash three times with ethanol, dry at 80 ° C for 12 h, and then disperse it in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS is 0.015 g / mL).
[0063] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0064] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0065] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0066] Example 5 The modified BNNS / PTFE composite film was prepared by the following steps: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0067] (2) Modification of BNNS: 2.5 g BNNS and 0.375 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. Then, the mixture was stirred at 25 °C for 12 h. The temperature was raised to 80 °C, 0.44 mmol tridecafluorooctyltrimethoxysilane and 2.42 mmol KH792 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 °C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0068] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0069] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0070] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0071] Example 6 The difference between this embodiment and embodiment 4 is that the proportion of heptadecafluorodecyltrimethoxysilane is increased while the total amount of heptadecafluorodecyltrimethoxysilane and KH792 remains unchanged. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this embodiment are as follows: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0072] (2) Modification of BNNS: 2.5 g BNNS and 0.2 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. Then, the mixture was stirred at 25 ° C for 12 h, and the temperature was raised to 80 ° C. 1.32 mmol heptafluorodecyltrimethoxysilane and 1.32 mmol KH792 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 ° C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0073] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0074] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0075] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0076] Example 7 The difference between this embodiment and embodiment 5 is that the proportion of KH792 is increased while the total amount of heptadecafluorodecyltrimethoxysilane and KH792 remains unchanged. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this embodiment are as follows: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0077] (2) Modification of BNNS: 2.5 g BNNS and 0.375 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. The mixture was then stirred at 25 °C for 12 h. The temperature was raised to 80 °C, 0.22 mmol tridecafluorooctyltrimethoxysilane and 2.64 mmol KH792 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 °C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0078] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0079] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0080] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0081] Example 8 The difference between this embodiment and embodiment 1 is that in this embodiment, heptadecafluorodecyltrimethoxysilane is replaced with an equal molar amount of 1H,1H,2H,2H-perfluorododecyltriethoxysilane. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this embodiment are as follows: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0082] (2) Modification of BNNS: 2.5 g BNNS and 0.255 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. The mixture was then stirred at 25 °C for 12 h. The temperature was raised to 80 °C, 0.17 mmol 1H,1H,2H,2H-perfluorododecyltriethoxysilane and 0.87 mmol KH792 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times and dried at 80 °C for 12 h. The mixture was then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0083] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0084] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0085] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0086] Example 9 The difference between this example and Example 5 is that in this example, tridecafluorooctyl trimethoxysilane is replaced with an equal molar amount of nonafluorohexyl trimethoxysilane. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this example are as follows: (1) Stripping of BNNS: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0087] (2) Modification of BNNS: 2.5 g BNNS and 0.375 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. Then, the mixture was stirred at 25 °C for 12 h. The temperature was raised to 80 °C, 0.44 mmol nonafluorohexyltrimethoxysilane and 2.42 mmol KH792 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 °C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0088] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0089] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0090] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0091] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, heptadecafluorodecyltrimethoxysilane is replaced with an equal molar amount of KH792. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this comparative example are as follows: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0092] (2) Modification of BNNS: 2.5 g BNNS and 0.255 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. Then, the mixture was stirred at 25 °C for 12 h, the temperature was raised to 80 °C, 1.04 mmol KH792 was added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 °C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0093] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0094] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0095] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0096] Comparative Example 2 The difference between this comparative example and Example 1 is that KH792 is replaced with an equal molar amount of heptadecafluorodecyltrimethoxysilane in this comparative example. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this comparative example are as follows: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0097] (2) Modification of BNNS: 2.5 g BNNS and 0.255 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. The mixture was then stirred at 25 °C for 12 h, heated to 80 °C, 1.04 mmol heptafluorodecyltrimethoxysilane was added, and stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times and dried at 80 °C for 12 h. The mixture was then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0098] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0099] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0100] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0101] Comparative Example 3 The difference between this comparative example and Example 1 is that KH792 is replaced by an equal molar amount of KH540 in this comparative example. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this comparative example are as follows: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0102] (2) Modification of BNNS: 2.5 g BNNS and 0.255 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. Then, the mixture was stirred at 25 ° C for 12 h, and the temperature was raised to 80 ° C. 0.17 mmol heptafluorodecyltrimethoxysilane and 0.87 mmol KH540 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 ° C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0103] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0104] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0105] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0106] Comparative Example 4 The difference between this comparative example and Example 1 is that KH792 is replaced by an equal molar amount of KH550 in this comparative example. Specifically, the steps for preparing the modified BNNS / PTFE composite film in this comparative example are as follows: (1) BNNS peeling: 4 g of h-BN powder was dispersed in 600 mL of DMF and stirred for 4 h. The mixture was then subjected to tip ultrasonic treatment for more than 2 h. Then, the obtained mixture was centrifuged at 3000 rpm for 0.5 h, and the supernatant was collected and centrifuged at 10000 rpm for 40 min. The lower layer was then collected and dried in a vacuum oven at 70 °C overnight to obtain BNNS.
[0107] (2) Modification of BNNS: 2.5 g BNNS and 0.255 g dopamine hydrochloride were weighed and added to a mixture of 20 mL Tris buffer and 7 mL 95% ethanol, and ultrasonicated for 30 min. Then, the mixture was stirred at 25 ° C for 12 h, the temperature was raised to 80 ° C, 0.17 mmol heptafluorodecyltrimethoxysilane and 0.87 mmol KH550 were added, and the mixture was stirred at 1200 rpm for 6 h. After the reaction, the mixture was washed with ethanol three times, dried at 80 ° C for 12 h, and then dispersed in deionized water to obtain a modified BNNS dispersion (the content of modified BNNS was 0.015 g / mL).
[0108] (3) Preparation of feed solution: Take 200 mL of PTFE emulsion (PTFE content is 1.43 g / mL), start stirring (speed 200 r / min), slowly add 10.75 mL of polyoxyethylene lauryl ether solution (Brij 30; polyoxyethylene lauryl ether content is 0.285 g / mL), then slowly add 8 mL of modified BNNS dispersion. After the addition is completed within 8 minutes, close the three-necked flask, turn on the connected circulating water vacuum pump, and perform vacuum degassing for 20 minutes to obtain a feed liquid.
[0109] (4) Scraping of wet film: PI film was selected as the base material, the scraper thickness was controlled to be 40 μm, the temperature was lower than 35°C, the scraper speed was 5 mm / s, and 5 mL of the slurry was scraped onto the surface of the PI film with a scraper to form a wet film.
[0110] (5) Heat treatment and cooling peeling: After the substrate with the wet film was dried at 45°C for 1 hour, it was heated to 240°C at a heating rate of 100°C / h and kept for 20 minutes, then heated to 350°C at a heating rate of 60°C / h, and finally heated to 380°C at a heating rate of 100°C / h and kept for 40 minutes. After the treatment, the film was cooled in an ice water bath and peeled off to obtain a modified BNNS / PTFE composite film.
[0111] Test Example 1: Dielectric energy storage performance of composite films with different amounts of modified BNNS added. Pure PTFE film and composite films prepared according to the methods of Examples 1 to 3 were taken, and copper electrodes were evaporated on the surface. The electrode diameter was about 2 mm and the thickness was 0.5 μm. Then, the dielectric energy storage performance test was performed. The dielectric spectrum obtained was as follows: Figure 1 As shown in Figure 2, the high temperature energy storage density and efficiency change with the field strength at 200℃ and 250℃. Figure 2 shown.
[0112] from Figure 1and Figure 2 It can be seen that by adding modified BNNS to PTFE film, its dielectric properties and high-temperature energy storage performance can be effectively improved.
[0113] Test Example 2: Effect of silane coupling agent on dielectric energy storage performance of composite film The composite film prepared according to the method in Examples 1, 4, 5 and Comparative Examples 1 to 4 was taken, and a copper electrode was evaporated on the surface. The electrode diameter was about 2 mm and the thickness was 0.5 μm. Then, the dielectric energy storage performance test was performed. The test results obtained are shown in Table 1.
[0114] Table 1 Test results of dielectric energy storage performance of composite films From Table 1 we can see that: (1) In Example 1, KH792 and heptadecafluorodecyltrimethoxysilane were used in combination, while only one of them was used in Comparative Examples 1 and 2, respectively. The high-temperature energy storage performance of Example 1 was significantly better than that of Comparative Examples 1 and 2. This is because: when KH792 and heptadecafluorodecyltrimethoxysilane were used in combination, the two could act on different positions in the PTFE molecular chain in different ways, thereby generating a synergistic effect of "1+1>2", which restricted the movement of the PTFE molecular chain to a greater extent and improved the high-temperature energy storage performance of the composite film.
[0115] (2) Compared with Example 4, Example 6 increases the proportion of the former between heptadecafluorodecyltrimethoxysilane and KH792, and the high-temperature energy storage performance is lower than that of Example 4; compared with Example 5, Example 7 increases the proportion of the latter between heptadecafluorodecyltrimethoxysilane and KH792, and the high-temperature energy storage performance is lower than that of Example 5. This is because: when the ratio between the fluorine-containing silane coupling agent and the aminosilane coupling agent is too large or too small, the synergistic effect between the two will be affected, thereby reducing the high-temperature energy storage performance of the composite film.
[0116] (3) The aminosilane coupling agents used in Example 1, Comparative Example 3 and Comparative Example 4 are KH792, KH540 and KH550 respectively, and the high-temperature energy storage performance of Example 1 is better than that of Comparative Examples 3 and 4. This is because: KH792 has strong alkalinity, can combine with carbon dioxide to form corresponding carbonates or carbamates, and stably bond with the fluorine atoms on PTFE, thereby improving the stability of the material and giving it better high-temperature energy storage performance.
[0117] (4) Compared with Example 1, Example 8 increases the length of the perfluoroalkyl group in the fluorinated silane coupling agent, and the high-temperature energy storage performance is lower than that of Example 1; compared with Example 5, Example 6 shortens the length of the perfluoroalkyl group in the fluorinated silane coupling agent, and the high-temperature energy storage performance is lower than that of Example 5. This is because: in the fluorinated silane coupling agent, when the carbon chain length of the perfluoroalkyl group is too short, its effect of reducing the high-temperature mobility of the molecular chain in the composite film is poor, which is not conducive to the improvement of the high-temperature energy storage performance of the film; when the carbon chain length of the perfluoroalkyl group is too long, the carbon chain is prone to decomposition or breakage at high temperature, affecting its ability to restrict the movement of the polymer molecular chain, and also causing the high-temperature energy storage performance of the film to decrease.
[0118] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A high energy storage modified BNNS / PTFE composite film, characterized in that: The invention comprises a polytetrafluoroethylene matrix and modified boron nitride nanosheets dispersed in the polytetrafluoroethylene matrix; the modified boron nitride nanosheets comprise boron nitride nanosheets, polydopamine bonded to the boron nitride nanosheets and a silane coupling agent grafted to the polydopamine; the silane coupling agent comprises a fluorine-containing silane coupling agent and an aminosilane coupling agent containing at least one amino group and at least one imine group.
2. The high energy storage modified BNNS / PTFE composite film according to claim 1, characterized in that: The fluorine-containing silane coupling agent contains a perfluoroalkyl group with 6 to 8 carbon atoms.
3. The high energy storage modified BNNS / PTFE composite film according to claim 1, characterized in that: The molar ratio of the fluorine-containing silane coupling agent to the aminosilane coupling agent is 1:4.5-5.
5.
4. The high energy storage modified BNNS / PTFE composite film according to claim 1 or 3, characterized in that: The aminosilane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
5. The high energy storage modified BNNS / PTFE composite film according to claim 1, characterized in that: The mass ratio of the polytetrafluoroethylene matrix to the modified boron nitride nanosheets is 100:0.03-0.
06.
6. A method for preparing the high energy storage modified BNNS / PTFE composite film according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Boron nitride nanosheets and dopamine monomers are used as raw materials to carry out polymerization reaction, and polydopamine is compounded on the surface of boron nitride nanosheets to obtain BNNS / PDA composite; (2) The silane coupling agent is grafted onto the BNNS / PDA composite through a dehydration condensation reaction between hydroxyl groups and silaneoxy groups to obtain modified boron nitride nanosheets; (3) The modified boron nitride nanosheets are composited with polytetrafluoroethylene to form a film.
7. The preparation method according to claim 6, characterized in that: The specific steps include: (1) Dispersing boron nitride nanosheets and dopamine monomers in a reaction solvent and reacting at 25-30 °C for 10-15 h to obtain a BNNS / PDA composite dispersion; (2) adding a silane coupling agent to the BNNS / PDA composite dispersion, reacting at 80-90°C for 5-8 h, separating the product, and dispersing it into a dispersion medium to obtain a modified boron nitride nanosheet dispersion; (3) The polytetrafluoroethylene emulsion and the modified boron nitride nanosheet dispersion are mixed, coated on a substrate by scraping, and after heat treatment, cooled, the obtained film is peeled off from the substrate.
8. The preparation method according to claim 6 or 7, characterized in that: In step (1), the mass ratio of the boron nitride nanosheets to the dopamine monomer is 1:0.08-0.15; the mass ratio of the boron nitride nanosheets in step (1) to the silane coupling agent in step (2) is 1:0.1-0.
3.
9. The preparation method according to claim 7, characterized in that: In step (3), before mixing the polytetrafluoroethylene emulsion and the modified boron nitride nanosheet dispersion, a thickener is first added to the polytetrafluoroethylene emulsion.
10. The preparation method according to claim 7, characterized in that: In step (3), the heat treatment process includes: drying at 45-50°C for 1-2 h, heating to 235-245°C at a rate of 90-110°C / h and keeping warm for 20-25 min, then heating to 345-355°C at a rate of 55-65°C / h, and finally heating to 375-385°C at a rate of 90-110°C / h and keeping warm for 40-50 min.
Citation Information
Patent Citations
High-energy-storage-density dielectric material and preparation method thereof
CN108300153A